Young people's access to sexual and reproductive health prevention services in South Africa during the COVID-19 pandemic: an online questionnaire. Issue 1 (24th January 2023) - Baker, Venetia; Mulwa, Sarah; Khanyile, David; Sarrassat, Sophie; O'Donnell, Dominique; Piot, Sara; Diogo, Yvonne; Arnold, Georgia; Cousens, Simon; Cawood, Cherie; Birdthistle, Isolde
Abstract : Introduction: The South African government responded swiftly to the first wave of novel coronavirus (SARS-CoV-2) with a nationwide lockdown. Initial restrictions from March–July 2020 required people to stay at home unless accessing essential, life-saving services. We sought to understand how the COVID-19 pandemic and resulting lockdowns affected young people's access to sexual and reproductive health services in a high-prevalence HIV setting. Methods: We analysed data from a cross-sectional web-based questionnaire conducted with 15–24 year-olds from September–December 2020 in Eastern Cape, South Africa. The questionnaire was promoted through social media platforms. Participants were asked whether and how the COVID-19 pandemic and related restrictions affected their access to sexual and reproductive health services, through closed-ended and open-ended questions. Descriptive statistics using proportions were used to summarise responses, and open text was analysed using thematic analysis. Results: Of 3431 respondents, the proportions reporting 'more difficulty' accessing HIV testing services, HIV self-screening kits, condoms, pre-exposure prophylaxis and antiretroviral treatment since the COVID-19 pandemic were 16.8%, 13.7%, 13.9%, 11% and 7%, respectively. In 796 open-text responses, participants described challenges accessing HIV services due to clinics being overwhelmed and prioritising patients with COVID-19, resulting in young people being turned away. Some were afraid of contracting COVID-19 at or en route to clinics. Others were unable to reach clinics because of restricted transport or financial insecurity. Discussion: Young people in Eastern Cape rely on local clinics for services, and large proportions of young males and females faced difficulties or fears accessing clinics during the COVID-19 lockdown. Clinics became overwhelmed or inaccessible, limiting young people's access to sexual and reproductive health services. In high HIV risk contexts, prevention services and tools must be more accessible to young people, outside of clinics and within the communities and spaces that young people can access without fear or cost.